How to Deal with Real Estate Booms : Lessons from Country Experiences - Rabanal, Pau (IMF Working Papers; Working Paper ;, 2011)
The financial crisis showed, once again, that neglecting real estate booms can have disastrous consequences. In this paper, we spell out the circumstances under which a more active policy agenda on this front would be justified. Then, we offer tentative insights on the pros and cons as well as implementation challenges of various policy tools that can be used to contain the damage to the financial system and the economy from real estate boom-bust episodes.